2005
DOI: 10.1038/sj.bjp.0706040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piperine, the pungent component of black pepper, at the human vanilloid receptor (TRPV1)

Abstract: 1 We have characterised the effects of piperine, a pungent alkaloid found in black pepper, on the human vanilloid receptor TRPV1 using whole-cell patch-clamp electrophysiology. 2 Piperine produced a clear agonist activity at the human TRPV1 receptor yielding rapidly activating whole-cell currents that were antagonised by the competitive TRPV1 antagonist capsazepine and the non-competitive TRPV1 blocker ruthenium red. 3 The current-voltage relationship of piperine-activated currents showed pronounced outward re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
186
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(212 citation statements)
references
References 54 publications
10
186
2
Order By: Relevance
“…The present study demonstrated that 6-shogaol, a pungent compound isolated from ginger, protects dopaminergic neurons against MPP + -and MPTP-induced neurotoxicity by inhibiting inflammatory pathways. Natural pungent compounds from plants have been suggested to play a role in protection via antioxidant, anti-inflammatory, and anti-carcinogenic activities [28,29] . For example, various experimental and clinical studies have shown that capsaicin and piperine isolated from pepper fruits, paradol isolated from Amomum melegueta Roscoe, and allicin isolated from garlic exhibit the most potent neuroprotective and anti-inflammatory effects identified for plant compounds to date [28,30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that 6-shogaol, a pungent compound isolated from ginger, protects dopaminergic neurons against MPP + -and MPTP-induced neurotoxicity by inhibiting inflammatory pathways. Natural pungent compounds from plants have been suggested to play a role in protection via antioxidant, anti-inflammatory, and anti-carcinogenic activities [28,29] . For example, various experimental and clinical studies have shown that capsaicin and piperine isolated from pepper fruits, paradol isolated from Amomum melegueta Roscoe, and allicin isolated from garlic exhibit the most potent neuroprotective and anti-inflammatory effects identified for plant compounds to date [28,30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the ion-channels responding to the last two chemicals are also thermoreceptors that respond to warm/hot and cool/cold temperatures, respectively. In fact, the capsaicin channel not only responds to chemically-related vanilloids (Szallasi and Blumberg, 1999), but also to unrelated VOCs (Silver et al, 2006;Trevisani et al, 2002), to other pungent compounds (Macpherson et al, 2005;McNamara et al, 2005) and even to inorganic volatiles (Trevisani et al, 2005).…”
Section: ) Molecular Receptors For Trigeminal Chemesthesismentioning
confidence: 99%
“…However, anandamide can also stimulate TRPV1 (Zygmunt et al, 1999), and ligands of cannabinoid receptors are thought to have the potential to be ligands of the TRPV1 channel as well (Di Marzo et al, 2007). As LASSBio-881 has a 1,3-benzodioxolyl moiety derived from safrole that is present in pungent TRPV1 agonists like piperine (McNamara et al, 2005), we sought to investigate whether this compound affects TRPV1 function.…”
Section: Introductionmentioning
confidence: 99%